The Influence of Promotions and Prices on Ticket Purchasing Decisions for Super Air Jet Air Transport Service Users at Batam's Hang Nadim International Airport - Liyya Apriliyeendy; Arif Fakhrudin (CV. Rayyan Dwi Bharata, 2023)
The Central Statistics Agency (BPS) noted that the number of enthusiasts in the aviation industry has increased, so airline entrepreneurs are also competing to meet this need. Super Air Jet (PT. Lion Air Group) is an LCC airline founded in 2021. This study aims to determine whether there is an influence of promotion and prices on ticket purchasing decisions for users of Super Air Jet air transportation services at Batam's Hang Nadim International Airport. This research method uses a quantitative approach. The number of samples in this study were 86 respondents. The respondents in this study were the public or users of the Super Air Jet air transport service. Determination of the sample using random sampling technique. Data collection technique by giving questionnaires to respondents. In analyzing this, validity and reliability tests, multiple linear regression tests, f (simultaneous) and t (partial) tests and the coefficient of determination (R2) are used. The test results show that: 1) Partially influences the decision to purchase tickets for super air jet air transport users at Batam's Hang Nadim International Airport. The partial test results show that Promotion (X1) has a significant value of the promotion variable of 0.000 ≤ 0.05 so it can be concluded that H1 is accepted or the promotion variable (X1) has an effect on customer satisfaction (Y) and Ho is rejected. Price (X2) has a significant value of the price variable of 0.000 ≤ 0.05 so that it can be concluded that H1 is accepted or the price variable (X2) has an effect on customer satisfaction (Y) and Ho is rejected. 2) Simultaneously influences the decision to purchase tickets for air transport users super air jet at Hang Nadim International Airport Batam. The results of these tests were obtained from the results of the F test with a significant value of 0.000 ≤ 0.05. So it can be concluded that H1 is accepted or in other words promotion (X1) and price (X2) simultaneously affect the purchase decision (Y) and Ho is rejected.